School-based allied health interventions for children and young people affected by neurodisability: a systematic evidence map. Issue 7 (27th March 2023) - McAnuff, Jennifer; Gibson, Jenny L.; Webster, Rob; Kaur-Bola, Kulwinder; Crombie, Sarah; Grayston, Aimee; Pennington, Lindsay
Abstract: Purpose: To systematically map available evidence for school-based interventions led by allied health (i.e., occupational therapy, physiotherapy, and/or speech and language therapy). Materials and methods: We searched for studies in pre-school, primary, secondary, or post-secondary settings, published 2004–2020. We coded study, population, and intervention characteristics. Outcomes were coded inductively, categorised, and linked to the International Classification of Functioning, Disability, and Health. Results: We included 337 studies (33 countries) in an interactive evidence map. Participants were mainly pre-school and primary-aged, including individuals with neurodisability and whole-school populations. Interventions targeted wide-ranging outcomes, including educational participation (e.g., writing, reading) and characteristics of school environments (e.g., educators' knowledge and skills, peer support). Universal, targeted, and intensive interventions were reported in 21.7%, 38.9%, and 60.2% of studies, respectively. Teachers and teaching assistants delivered interventions in 45.4% and 22.6% of studies, respectively. 43.9% of studies conducted early feasibility testing/piloting and 54.9% had ≤30 participants. Sixty-two randomised controlled trials focused on intervention evaluation or implementation. Conclusions: In the United Kingdom, future research should take forward school-based allied health interventions that relate directly to agreed research priorities. Internationally, future priorities include implementation of tiered (universal, targeted, intensive) intervention models and appropriate preparation and deployment of the education workforce. IMPLICATIONS FOR REHABILITATION: Allied health professionals (occupational therapists, physiotherapists, and speech and language therapists) work in schools supporting children and young people affected by neurodisability but the content, impact, and cost-effectiveness of their interventions are not well-understood. We systematically mapped the available evidence and identified that allied health school-based interventions target highly diverse health-related outcomes and wider determinants of children and young people's health, including educational participation (e.g., literacy) and characteristics of the school environment (e.g., educators' knowledge and skills). Our interactive evidence map can be used to help stakeholders prioritise the interventions most in need of further evaluation and implementation research, including tiered models of universal, targeted, and intensive allied health support. Teachers and teaching assistants play a central role in delivering allied health interventions in schools – appropriate preparation and deployment of the education workforce should therefore be a specific priority for future international allied health research.